An optimised semantic web services discovery in MANET. (2017) - Ayad, Soheyb; Kazar, Okba; Benharkat, AÁ¯cha-Nabila; Terrissa, Sadek-Labib
The web services discovery process in mobile ad hoc networks is considered as a very difficult challenge due to the continuous change in the topology of the network and also the lack of a fixed central directory for publishing web services. Several approaches have been proposed, all these solutions are based on either keywords or identifiers representing the service to be searched or by using a specific scenario of discovery, all by trying to respect the constraints of ad hoc networks such as energy, bandwidth, throughput, etc. In this paper, we will present a new web services discovery protocol based on the dissemination of semantic web services information in routing process using the cross-layer routing techniques. We will also present the simulation results obtained where we have noticed a significant optimisation of the energy consumption level and of the average throughput using the DISCOVERY_DIAMETER parameter that we have proposed to limit the area of discovery in the network.